THE EFFECTIVENESS OF SCRAPBOOK IN INCREASING THE STUDENTS' ENTHUSIASM FOR LEARNING FUNCTIONAL TEXT IN X GRADE AT SMA NEGERI 2 NGANJUK - Miftahul Khasanah; Henny Roesellaningtias; Caltira Rosiana (Dharma Pendidikan, 2024)
The aims of this study were: 1. To analyze the enthusiasm of class X students before using scrapbook media in learning English functional text material at Nganjuk 2 Public High School, 2) To analyze the enthusiasm of class X students after using scrapbook media in learning English functional text material at Nganjuk 2 Public High School, 3) To determine the effectiveness of scrapbooks in increasing student enthusiasm in learning English functional text material at Nganjuk 2 Public High School. The research design uses quantitative and this type of research uses pre-experimental with one-group pretest-posttest. This research was conducted at Nganjuk 2 Public High School in the 2022/2023 academic year, using a population of all class X students of Nganjuk 2 Public High School, the sample used by the author was class X-9, the treatment class consisted of 31 students. The sampling technique used purposive sampling. Collecting data in this study using a questionnaire test. The analytical technique used to analyze the data in this study is descriptive statistics, inferential statistics using the t-test. Based on test scores. Students get an average pre-test score of 75.935 and an average post-test score of 84.193. Based on the results of the analysis, it is known that the significant level is 5% for Df = 30, the value of tcount = 6.622 and ttable = 1.697, then tcount ttable which means Ha is accepted. So that "Scrapbooks are effective in increasing student interest in learning functional texts in class X SMA Negeri 2 Nganjuk in the 2022/2023 Academic Year".